Supplier inventory leanness and financial performance - Barker, Jordan M.; Hofer, Christian; Hoberg, Kai; Eroglu, Cuneyt (Journal of Operations Management, 2022)
AbstractNumerous studies have examined the relationship between inventory management and financial performance. However, the focus of such empirical work has primarily been on how a firm's own inventory characteristics affect its performance. Our objective is to extend this body of literature beyond the firm‐level. We draw on inventory theory and resource‐based theories to hypothesize about the effect of supplier inventory leanness on a focal firm's financial performance and how supplier and focal firm inventory leanness interact to affect such outcomes. We test our hypotheses using a large panel dataset of supplier‐focal firm relationships obtained from Compustat's Customer Segment database and aggregated to the focal firm‐quarter level, as well as firm financial information from Compustat's Fundamentals Quarterly database. The econometric analyses provide evidence that supplier inventory leanness influences focal firm financial performance indirectly through the interaction with the firm's own inventory leanness. In particular, our estimation results detail how supplier inventory leanness affects the non‐linearity of the focal firm's inventory leanness‐financial performance relationship and its optimal inventory leanness level. The findings broaden the scope of empirical inventory literature and highlight supplier inventory leanness as an important consideration in firm‐level inventory decision making.